Combination Therapy With Semaglutide and Dapagliflozin as an Effective Approach for the Management of Type A Insulin Resistance Syndrome: A Case Report - Martínez-Montoro, José Ignacio; Pinzón-Martín, José Luis; Damas-Fuentes, Miguel; Fernández-Valero, Andrea; Tinahones, Francisco J. (Frontiers in Endocrinology, 2022)
Type A insulin resistance (IR) syndrome is a very uncommon genetic disorder affecting the insulin receptor (INSR) gene, characterized by severe IR without the presence of obesity. Patients with this condition will eventually develop diabetes, presenting a variable response to insulin-sensitizers, such as metformin and thiazolidinediones, and high doses of insulin. We report for the first time the results of the use of combination therapy with a glucagon-like peptide-1 receptor agonist and a sodium-glucose cotransporter 2 inhibitor for the treatment of diabetes in the context of type A IR syndrome.